Remarkable strengthening effects of cells in laser powder bed fusion-processed Inconel 718 - Taichi Kikukawa; Takuya Ishimoto; Hyoung Seop Kim; Takayoshi Nakano (Materials Research Letters)
Alloys fabricated via laser powder bed fusion (LPBF) exhibit superior strength. This study investigates the individual strengthening effects of the nanometre-sized cellular and micrometre-sized crystallographic lamellar structures in the LPBF-fabricated Inconel 718 alloy by selectively eliminating these structures through heat treatment and a novel laser scanning strategy, respectively. While cellular structures increased the yield strength by approximately 38%, lamellar structures contributed to only a marginal 2% increase. This finding demonstrates the remarkable strengthening effect of cells on LPBF products. This study highlights that cells are not merely microstructures but are critical features governing the exceptional strength of LPBF products.